Mechanical performance of binder yarn composites - Knipprath, Christian (Cranfield University, 2010)
This investigation concerns the mechanical response of binder coated carbon tow preforms and laminates. The main focus is on evaluating and modelling the robustness of preforms whilst the methodologies developed are also applied to cured laminates produced using the binder coated preforms. Conventional manufacturing techniques were altered to address the differences in behaviour due to the presence of the binder with the development of infusion schedules. These involve lower temperatures, which eliminate the possibility of binder reactivation during processing. Different development versions of the material in the form of an inhomogeneously or homogeneously bindered tow were characterised in terms of their mechanical response in the preform state. It was observed that the inhomogeneously bindered material had higher modulus and strength in both tension in the fibre direction and shear, while the behaviour of the homogeneous preform is significantly more robust in the transverse to the fibre direction. Laminates produced, using the homogeneously bindered material, were compared to a reference unbindered laminate system, using an aerospace epoxy as a matrix. The out-of-plane properties of the material with binder were superior to the reference laminate, whereas in-plane properties were similar or inferior. The development of models of the mechanical response built around continuum damage mechanics models allowed the simulation of the behaviour of preforms under loading. The implementation of these constitutive models necessitated the development of appropriate parameter estimation techniques capable of solving the inverse problem of identifying the values of 27 material constants that minimise the error between experimental and modelling results. Two novel methodologies were developed and compared to a conventional technique following simplified laminate analysis. The first method performed a gradient-based error minimisation and the second uses the Markov Chain Monte Carlo technique. The gradient-based technique results in a close fit, while this method requires proper definition of the constraints to yield an appropriate solution set. Markov Chain Monte Carlo yields satisfactory results with the additional advantages of overcoming the ill-posedness of the inverse problem without regularisation and providing an output in the form of multivariate probability distributions that can be used directly instochastic simulations. The material parameters obtained and the corresponding constitutive models were used in finite element models of the mechanical response of preforms and laminates. The models were based on the concept of a combination of shell elements representing sub-laminates and cohesive elements simulating the delamination behaviour of interfaces between them. The performance of the models was evaluated using the case of impact of a spar section for preforms and three point bending for the laminates. The agreement between experimental and simulation results was satisfactory. The validated model was used in the context of a design case study based on a helicopter pitch horn component. The aim was to use the results of a draping analysis in the finite element model to evaluate the effects of the assumption of nominal fibre orientations on design and to combine the results of drape optimisation in respect to fibre shear angle with finite element analysis incorporating damage. The results showed that the use of nominal fibre orientation predicts a good performance of the component, whereas the influence of optimising draping on the mechanical performance was inferior.